Potensi Bisnis Maggot Menggunakan Limbah Organik Pasar Mawar - Fauzy, Ahmad; Jumiati, Jumiati; Sulastri, Aini (Jurnal Teknologi Lingkungan Lahan Basah, 2026)
Organic waste accounts for the largest share of municipal solid waste and poses environmental risks if not properly managed. This study aims to analyze the potential of organic waste at the Pasar Mawar Temporary Waste Disposal Site (TPS) as feed for maggot cultivation, to assess the technical feasibility of maggot farming across several locations in Pontianak City, and to evaluate the business feasibility using the Break-Even Point (BEP) approach. The research methods include measuring waste generation in accordance with SNI 19-3964-1994, structured interviews with maggot producers, and a simple economic analysis. The results show an average organic waste generation of 235.25 kg/day, dominated by vegetable and fruit residues. The surveyed maggot cultivation sites exhibited varied production levels, with significant waste-reduction efficiency. BEP analysis indicates that maggot farming is economically viable and feasible at the community scale. These findings support the utilization of maggots as an effective solution for organic waste management and as a potential component of a circular economy model.